2017
DOI: 10.1542/peds.2016-4146
|View full text |Cite
|
Sign up to set email alerts
|

Oral Corticosteroid Prescribing for Children With Asthma in a Medicaid Managed Care Program

Abstract: The patterns of dispensing observed suggest substantial overprescribing of OCS for children with an asthma diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 14 publications
(10 reference statements)
0
37
0
Order By: Relevance
“…SCS exert an anti-inflammatory effect in asthmatic airways by inhibiting the production of potent pro-inflammatory mediators and by reducing the chemotaxis of inflammatory cells to the lungs [10]. Possibly because of their efficacy, relative affordability or a perception that short courses are harmless, substantial over-prescribing of SCS has been reported in both adults and children with asthma [9,11]. Emergency SCS are prescribed as part of asthma self-management plans for patients at risk of exacerbations [12]; when not correctly implemented, this may lead to incorrect use of the medication, putting patients at risk of adverse events.…”
Section: Use Of Scs In Asthma Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…SCS exert an anti-inflammatory effect in asthmatic airways by inhibiting the production of potent pro-inflammatory mediators and by reducing the chemotaxis of inflammatory cells to the lungs [10]. Possibly because of their efficacy, relative affordability or a perception that short courses are harmless, substantial over-prescribing of SCS has been reported in both adults and children with asthma [9,11]. Emergency SCS are prescribed as part of asthma self-management plans for patients at risk of exacerbations [12]; when not correctly implemented, this may lead to incorrect use of the medication, putting patients at risk of adverse events.…”
Section: Use Of Scs In Asthma Managementmentioning
confidence: 99%
“…Highly accessible and available over the counter in some countries, SCS are prescribed as rescue medication and are largely self-administered at home. It is noteworthy that SCS courses are used to treat not only severe, but also moderate and even mild exacerbations and symptoms [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although up to 44% of the children had ≥1 OCS-dispensing event, only 28% of children had an ICS-dispensing event. 1 In a similar study of children with asthma enrolled in 85 different health care plans in the United States, the frequency of OCS-prescribing events was 23%; however, the frequency of ICS treatment was 25%. 2 In another study, Elkout et al 8 reported a frequency of OCS prescription of 16% in Scotland; however, the frequency of ICS treatment during the same time period was ∼73%, >4 times the frequency of OCS use.…”
mentioning
confidence: 99%
“…In this issue of Pediatrics, Farber et al 1 present the results of an analysis of claims data for children with asthma who were enrolled in a large managed care Medicaid and Children's Health Insurance Program from 2011 to 2016. During each of the years analyzed, 42.1% to 44.2% of the children had ≥1 event in which an oral corticosteroid (OCS) for asthma was dispensed.…”
mentioning
confidence: 99%
“…3 A data claims analysis from the Texas Children's Health Plan of 1 to <18 year olds revealed that 42.1 to 44.2% of children with asthma were dispensed at least one OCS course annually, with both higher dispensing rates and repeated OCS dispensing in children aged 1 to 4 years as compared with older children, suggesting substantial overprescribing of OCS. 4 A retrospective analysis of the Medical Expenditure Panel Study revealed 3.4 million school-aged children had an asthma exacerbation in 2013, and these children with exacerbations had 18.9 times more annual asthma-specific emergency department visits and 43.3 times more asthma-specific hospitalizations than those without an exacerbation. 5 On the basis of the nationally representative Medical Expenditure Panel Survey sample weights from 2013, the total annual health care expenditures attributable to asthma for school-aged children in the United States was $5.92 billion.…”
mentioning
confidence: 99%